2021
DOI: 10.1177/00208728211048934
|View full text |Cite
|
Sign up to set email alerts
|

Responding to COVID-19 in social work field education in Australia, New Zealand and the United States

Abstract: This descriptive article reports immediate responses to COVID-19 by social work field education faculty in four universities in Australia, New Zealand and the United States. Moving swiftly to online innovations, tele-supervision, teaching remote practice methods, and establishing alternative placements allowed students to meet required competencies while supporting students during the immediate crisis. Collaboration between field education faculty teams, professional bodies and agencies and clear communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…A cross-sectional web-based survey that included closed- and open-ended questions was used to understand the impact of COVID-19 on field education from the perspectives of BSW and MSW students across Canada. The survey design was informed by the researchers’ experiences and the relevant literature, which included prior surveys conducted on social work field education during the 2009 H1N1 pandemic (Drolet et al, 2013) and the current impacts of COVID-19 on Canadian postsecondary students (Frontiers 2020; Statistics Canada, 2020). While researchers’ social locations can contribute to bias, these can be mitigated through an awareness of biases and exposure to a range of perspectives and ideas (Michalski, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional web-based survey that included closed- and open-ended questions was used to understand the impact of COVID-19 on field education from the perspectives of BSW and MSW students across Canada. The survey design was informed by the researchers’ experiences and the relevant literature, which included prior surveys conducted on social work field education during the 2009 H1N1 pandemic (Drolet et al, 2013) and the current impacts of COVID-19 on Canadian postsecondary students (Frontiers 2020; Statistics Canada, 2020). While researchers’ social locations can contribute to bias, these can be mitigated through an awareness of biases and exposure to a range of perspectives and ideas (Michalski, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With the rapid onset of the pandemic and the resulting disruptions in post-secondary education, many social work programs in Canada and internationally necessarily adopted technology to continue learning opportunities, including virtual field placements (CASWE-ACFTS, 2020a; Crisp et al, 2021;CSWE, 2020;Fronek et al, 2021). This sudden shift to fully virtual field education introduced new challenges and complexities for student learning (Crisp et al, 2021;Fronek et al, 2021). Canadian social work schools also faced critical issues implementing online teaching in the face of limited resources and notably short timelines to implement this shift (CASWE-ACFTS, 2020a).…”
Section: Use Of Technology In Field Educationmentioning
confidence: 99%
“…Additionally, supervisors developed a strategy of virtual supervision for their fieldwork students. Some of the scholars (Fronek et al, 2021;Kourgiantakis & Lee, 2020;Zvomuya, 2021) identified changes introduced in social work teaching and practice, such as counseling, following up, community linkage, etc. through online platforms during the pandemic.…”
Section: Of 11mentioning
confidence: 99%
“…To meet the demand of the newly emerged environment, people started adopting novel strategies for survival replacing traditional ones. Different studies (notably, Csoba & Diebel, 2020; Fronek et al, 2021) revealed that the COVID‐19 pandemic not only limited social work services but also opened up new opportunities, like innovating online tools, making it easier to reach out to the individuals and specific groups of people. Additionally, supervisors developed a strategy of virtual supervision for their fieldwork students.…”
Section: Introductionmentioning
confidence: 99%
“…Students training to become nurses and social workers also experienced increased levels of stress, anxiety, and depression associated with the COVID-19 pandemic (Evans et al, 2021; Joseph et al, 2022; Savitsky et al, 2020). Nursing and social work students observed and experienced the strain on the workforce during clinical practicums, as well as the impact to the population through various social media platforms (Fronek et al, 2023; Jokar et al, 2023). Students also experienced barriers to access to social support due to social distancing, and struggled with decreased resilience as a result of mental, emotional, and spiritual exhaustion (Rosa et al, 2020).…”
mentioning
confidence: 99%